KRITERIA BUKU AJAR BAHASA ARAB DALAM KITAB IDHA`AT - Aris Junaedi Abdilah; Maman Abdurrahman (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2023)
This research aims to determine the criteria for a good Arabic language textbook according to Sheikh Fauzan in the book "Idhaat". The research utilizes a literature review method. The results of the study indicate that a good Arabic language textbook in the book "Idhaat" must fulfill 23 criteria. The textbook, as the core of learning, needs to receive serious attention in order to create quality Arabic language instruction. Furthermore, the criteria for a good textbook are important to be applied in order to achieve the desired learning objectives. The criteria for a textbook in the book "Idha`at" can serve as a reference for the creation of quality Arabic language textbooks.